KEDUDUKAN DAN PEMUJAAN BRAHMA PADA JAMAN HINDHU - lstari, T.M. Rita (Naditira Widya, 2007)
Hindu perceives art having essential role in worship art is one of human means to express ideas of one's belief. Neverteless, art also has educational value to be embedded upon its community's mind set. This article will discoss the role of Brahma and Brahma Worshipping in lndgnesia during the to Indies Influence.